Temporal patterns in Saturnidae (silk moth) and Sphingidae (hawk moth) assemblages in protected forests of central Uganda. Issue 8 (25th March 2015) - Akite, Perpetra; Telford, Richard J.; Waring, Paul; Akol, Anne M.; Vandvik, Vigdis
Abstract: Forest‐dependent biodiversity is threatened throughout the tropics by habitat loss and land‐use intensification of the matrix habitats. We resampled historic data on two moth families, known to play central roles in many ecosystem processes, to evaluate temporal changes in species richness and community structure in three protected forests in central Uganda in a rapidly changing matrix. Our results show some significant declines in the moth species richness and the relative abundance and richness of forest‐dependent species over the last 20–40 years. The observed changes in species richness and composition among different forests, ecological types, and moth groups highlight the need to repeatedly monitor biodiversity even within protected and relatively intact forests. Abstract : Re‐sampling surveys for two moths families was carried out in three protected forests in central Uganda to evaluate temporal changes in patterns of richness and community structure. We formulated and tested hypotheses. Our results show some significant declines in moth richness and abundances with forest dependent species more impacted on over the years.